Where Life Coaching Ends and Therapy Begins: Toward a Less Confusing Treatment Landscape - Aboujaoude, Elias (Perspectives on psychological science, 2020)
“Life coaching” is a rapidly expanding profession born out of an unmet need for help effecting change, frustration with traditional models, the stigma attached to seeking care, and the online “Uberization” of many new services. But the distinctions often drawn between life coaching and psychotherapy are increasingly blurry, raise important questions about where coaching ends and therapy begins, and risk confusion between the two helping professions among vulnerable patients. This is potentially serious, in part because life coaching operates in a regulatory vacuum, with no education, training, licensing, or supervision requirements for coaches and no specific legal protections for any harmed clients. Although increased access to new forms of help is a positive development, the risk that mentally ill patients may undergo life coaching rather than receive proven psychotherapy treatments raises concerns about patient safety. It can also trigger fears of professional replacement among mental health providers whose education, preparation, and practice parameters are rigorously defined and closely scrutinized. More research is needed to prove the efficacy and safety of life-coaching modalities, and meaningful action is required at the level of training, oversight, and legislation to help protect patients and clarify roles.